Understanding video games : - Smith, Jonas Heide (Routledge, 2013)
"From Pong to PlayStation 3 and beyond, Understanding Video Games traces the history of video games, introduces the major theories used to analyze games such as ludology and narratology, reviews the economics of the game industry, examines the aesthetics of game design, surveys a broad range of game genres, explores player culture, and addresses the major debates surrounding the medium, from educational benefits to the effects of violence. Throughout the book, the authors ask students to consider larger questions about the medium:What defines a video game?Who plays games?Why do we play games?How do games affect the player?Extensively illustrated, and featuring discussion questions, a video game history timeline, and a glossary of key terms, Understanding Video Games is an indispensable and comprehensive resource for those interested in the ways video games are reshaping entertainment and society. "--